2019
DOI: 10.37897/rjr.2019.1.4
|View full text |Cite
|
Sign up to set email alerts
|

The role of nailfold capillaroscopy in monitoring lung involvement in systemic sclerosis

Abstract: The usefulness of capillaroscopy in the follow-up of scleroderma patients and the possible prognostic role for the appearance of visceral involvement is suggested by many authors but still under debate.The aim of this study was to assess the role of monitoring capillaroscopic abnormalities (qualitative and semiquantitative) in relation with parameters of interstitial lung involvement and pulmonary arterial hypertension(PAH). A strong correlation was identified between initial capillaroscopy scores and FVC (r=-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It was unusual that the risk of SSc-PAH was approximately 5.8 times greater in dcSSc associated with SSc-ILD, though there was no significantly greater risk of SSc-PAH in the presence of dyspnea (p = 0.064). Severe NC changes have been reported to increase the risk of SSc-PAH (36)(37)(38). Similarly, it was found that the risk of PAH was about three times greater with abnormalities in NC.…”
Section: Discussionmentioning
confidence: 86%
“…It was unusual that the risk of SSc-PAH was approximately 5.8 times greater in dcSSc associated with SSc-ILD, though there was no significantly greater risk of SSc-PAH in the presence of dyspnea (p = 0.064). Severe NC changes have been reported to increase the risk of SSc-PAH (36)(37)(38). Similarly, it was found that the risk of PAH was about three times greater with abnormalities in NC.…”
Section: Discussionmentioning
confidence: 86%